Mapping West Java Northern waters quality using sea water quality standards - Mercy Patanda; Dwi Ernaningsih; Mario Limbong (Depik, 2024)
Poor water quality caused by the influence of activities on land and sea can disrupt the ecosystem and the existence of fish resources in coastal areas. Damage to fish habitat impacts fishing areas, resulting in a decrease in fishermens catches. Fish resources will move further away from the coast, resulting in a narrower utilization of sea space for small fishermen and leading to conflicts. Thus, this study aims to analyze the quality of the aquatic environment and map the pollution degradation in the northern waters of West Java Province. The survey method was used in this study. The types of water quality data measured were water clarity, sea surface temperature, salinity, light attenuation coefficient, total suspended solids, and chlorophyll-a. In-situ seawater quality measurements in coastal waters were carried out at 30 points. In-situ water quality data was compared with remote sensing image data. Water quality parameter data was analyzed descriptively by comparing the results obtained with seawater quality standards for marine biota based on the Decree of the Minister of Environment No. 51 of 2004 concerning Seawater Quality Standards. The results showed that the light attenuation coefficient and salinity parameter had an average that did not comply with the seawater quality standards for biota. The parameters of chlorophyll-a, brightness, suspended solids load, and sea surface temperature were still within the threshold of seawater quality standards for biota life (good condition). The environmental conditions of the northern waters of West Java Province are classified as good, were around 3,261.703 km2, while the lightly polluted area was around 3,043.452 km2. The northern waters of West Java Province, classified as lightly polluted, were concentrated in two locations, the northern waters of Bekasi, and Indramayu.Keywords:Quality standardsDegradationWest JawaWater qualityMapping